2018
DOI: 10.1002/asia.201701754
|View full text |Cite
|
Sign up to set email alerts
|

Dianionic Titanyl and Vanadyl (Cation+)2[MIVO(Pc4−)]2− Phthalocyanine Salts Containing Pc4− Macrocycles

Abstract: In this study, the titanyl and vanadyl phthalocyanine (Pc) salts (Bu N ) [M O(Pc )] (M=Ti, V) and (Bu MeP ) [M O(Pc )] (M=Ti, V) with [M O(Pc )] dianions were synthesized and characterized. Reduction of M O(Pc ) carried out with an excess of sodium fluorenone ketyl in the presence of Bu N or Bu MeP is exclusive to the phthalocyanine centers, forming Pc species. During reduction, the metal +4 charge did not change, implying that Pc is an non-innocent ligand. The Pc negative charge increase caused the C-N(pyr) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…Noticeable elongation of the C–N pyr bonds is observed in the radical trianionic state (by 0.02 Å on an average). 4e Moreover, alternation of the C–N imine (for Pc and Nc) 4,5 or the C–C meso bonds (for TPP) 14 is also manifested in such a way that four bonds belonging to two oppositely located isoindole (Pc and Nc) or pyrrole (TPP) units become short and four other bonds belonging to two other oppositely located units become long. The difference between average short and long bonds of 0.03–0.04 Å essentially exceeds the 3σ value, where σ is the standard deviation in the lengths of these bonds.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeable elongation of the C–N pyr bonds is observed in the radical trianionic state (by 0.02 Å on an average). 4e Moreover, alternation of the C–N imine (for Pc and Nc) 4,5 or the C–C meso bonds (for TPP) 14 is also manifested in such a way that four bonds belonging to two oppositely located isoindole (Pc and Nc) or pyrrole (TPP) units become short and four other bonds belonging to two other oppositely located units become long. The difference between average short and long bonds of 0.03–0.04 Å essentially exceeds the 3σ value, where σ is the standard deviation in the lengths of these bonds.…”
Section: Results and Discussionmentioning
confidence: 99%
“…2c Reduction of metal macrocycles results in the formation of radical trianions with S = 1/2 spin state. When such radical trianionic macrocycles are packed in π-stacking dimers or two-dimensional (2D) layers with effective π–π interaction between them, strong enough magnetic coupling of spins can be attained with exchange interaction ( J / k B ) up to −255 K 4 or even stronger for the naphthalocyanine (Nc) radical trianions. 5 In these salts, counter cations are present to compensate negative charge and solvent molecules are frequently involved in the crystals to occupy vacancies in the packing of the ionic components.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of dianionic phthalocyanine and tetrapyrazinoporphyrazine macrocycle to the radical trianionic and tetraanionic state leads to a strong blue shift of both Soret and Q‐bands and the appearance of new bands in the NIR range at 930–1070 nm , . As a rule, the intensity of the NIR bands for the tetraanionic macrocycle is essentially weaker in comparison with that for the radical trianionic macrocycle , . The bands in the NIR range appear due to that electron injection to LUMO allows new low‐energy transitions from this partially occupied level to the LUMO + 1 level.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially reduced metal phthalocyanines can also manifest promising conducting and magnetic properties. Metal macrocycles can be reduced successfully by strong reductants such as Na/Hg, potassium graphite (KC 8 ) , , LiCp * , decamethylchromocene,, and sodium fluorenone ketyl . Zinc dust can also be used as suitable reductant especially to obtain reduced compounds of iron(II) phthalocyanine or hexadecachlorophthalocyanine , …”
Section: Introductionmentioning
confidence: 99%
“…[7] Reduction chemistry of metal macrocycles have been studying only recently. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Recently it was shown that in salts obtained by reduction of iron(II) phthalocyanine and iron(II) hexadecachlorophthalocyanine macrocycles pack in layers, [22,23] one-dimentional chains [22] or closely packed p-p stacking columns. [24] In these salts only iron(II) atomes are reduced, no electron transfer to the phthalocyanine macrocycles is observed even inspite of the presence of sixteen chlorine atoms on periphery of macrocycle which increase essentially acceptor propertie of the macrocycle.…”
Section: Introductionmentioning
confidence: 99%